2008
DOI: 10.4141/cjps08099
|View full text |Cite
|
Sign up to set email alerts
|

Control of common cocklebur (Xanthium strumarium L.) with pre- and postemergence herbicides in soybean

Abstract: ]. There was minimal injury (2% or less) to soybean from the PRE and POST herbicides evaluated. Cloransulam applied PRE provided up to 98% visual control, reduced density 93%, and reduced dry weight of cocklebur 96%. Linuron, metribuzin, imazethapyr, and clomazone applied PRE provided 0 to 77% control and reduced density and dry weight of cocklebur minimally (54% or less) compared with the weedy check. Cloransulam applied POST provided as much as 98% control, reduced density up to 96%, and reduced dry weight o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Abdel -Hamid and El-Metwally (2008) and Sikkema et al (2008) found that the fresh and dry weights of weeds were significantly reduced by using pre-emergence herbicides. Concerning post-emergence herbicides, Sikkema et al (2008) reported that application of post-emergence herbicides reduced dry weight of weeds especially the season weeds, either brod-leaved or grassy weeds in soybean fields.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abdel -Hamid and El-Metwally (2008) and Sikkema et al (2008) found that the fresh and dry weights of weeds were significantly reduced by using pre-emergence herbicides. Concerning post-emergence herbicides, Sikkema et al (2008) reported that application of post-emergence herbicides reduced dry weight of weeds especially the season weeds, either brod-leaved or grassy weeds in soybean fields.…”
Section: Introductionmentioning
confidence: 99%
“…Abdel -Hamid and El-Metwally (2008) and Sikkema et al (2008) found that the fresh and dry weights of weeds were significantly reduced by using pre-emergence herbicides. Concerning post-emergence herbicides, Sikkema et al (2008) reported that application of post-emergence herbicides reduced dry weight of weeds especially the season weeds, either brod-leaved or grassy weeds in soybean fields. With regard to herbicides combinations, either as pre-or post-emergence only, or pre + post-emergence combination, several researchers, indicated that the herbicides combination were more effective for weed control in soybean than individual herbicide applications ( Sarah et al 2002;Reddy et al, 2003 andSaudy andEl-Metwally, 2009).…”
Section: Introductionmentioning
confidence: 99%